Comprehensive molecular-genetic analysis of a hearing loss cohort from Argentina: Functional validation of novel variants identified - Buonfiglio, Paula Inés (2022)
Hearing loss (HL) is the most prevalent sensorineural deficit, affecting about 20% of the global Population, with nearly half due to genetic causes. About 1 in 500 newborns present congenital HL and more than 100 genes are involved. Most of the patients are non-syndromic with an autosomal recessive mode of inheritance (80%), caused most frequently by GJB2 and GJB6 genes. Inthis work, we aimed to identify the genetic cause of HL designing a multistep approach to analyze target genes.Besides, we performed in silico and in vivo analyses in order to further study some of the identified variants in the zebrafish model. A total of 650 patients were studied by Sanger Sequencing and Gap-PCR in GJB2 and GJB6 genes respectively, diagnosing 15.5% of sporadic cases and 36% of familial ones. Overall, 50 different sequence variants were detected. Next, 50 patients with moderate HL were tested for deletions in STRC gene by MLPA technique. After initial screening, 38 families were selected to be analyzed by Whole Exome Sequencing, achieving Diagnosis in 40%. Half of the identified variants were novel. One of them was a missense variant detected in a familial case in MYO6 gene. To further analyze the functional implication of this variant, a protein modeling with I-Tasser software was performed revealing its pathogenic effect. In order to functional validate this candidate variant a knockdown phenotype rescue assay using anantisense oligonucleotide (morpholino) in zebrafish was carried out demonstrating the deleterious effect on the auditory system. In the present study, we showcased that our algorithm is suitable for the sequential multigenic approach to HL in our cohort. This involves both everyday routine molecular biology and next generation sequencing techniques to identify the genetic etiology ofHL. Furthermore, in silico and in vivo analyses provide not only evidence to validate novel variants but also new knowledge to better understand the genetic basis of HL.